The development of internet advertisement in Poland throughout recent years - A. Kisiołek (Marketing i Menedžment Innovacij, 2014)
The article presents basic information regarding online advertisement and its most popular forms in Poland. Some part of the work is devoted to the development of Polish Internet advertisement since 2000, and particularly in 2010-2012. Historical trends in the development of online advertising in Poland are analyzed as well.